Numerical Analysis of In Situ Conversion Process of Oil Shale Formation Based on Thermo-Hydro-Chemical Coupled Modelling - Juan Jin; Weidong Jiang; Jiandong Liu; Junfeng Shi; Xiaowen Zhang; Wei Cheng; Ziniu Yu; Weixi Chen; Tingfu Ye (Energies, 2023)
The in situ conversion process (ICP) is a retorting method pyrolyzing the kerogen in shale into oil and gas products, which shows great potential to promote the recovery of oil shale resources. In this work, a thermo-hydro-chemical-coupled model for the in situ conversion process is established, considering the temperature dependence of key properties and the transverse isotropy caused by the layered characteristics of oil shale. Based on the proposed model, a series of simulations is conducted to evaluate the production performance of the in situ conversion process of oil shale reservoirs. The results indicate that energy efficiency reaches a maximum of 2.7 around the fifth year of the heating process, indicating the feasibility of in situ conversion technology. Furthermore, the sensitivity analysis shows that the heating temperature should be higher than 300 °C to avoid the energy output being less than the energy input, and the oil/gas ratio decreases with increasing heating temperature. Moreover, thermal conductivity is positively with production while heat capacity is negatively correlated, and the energy efficiency decreases with increasing thermal conductivity and matrix heat capacity. Finally, the heating period should be no longer than 4 years to maximize the heating efficiency.